ANALYSIS OF EMOTIONAL INTELLIGENCE DETERMINANTS IN NURSING PROFESSION STUDENTS IN BANDA ACEH AND ACEH BESAR - Desreza, Nanda; Renamisdayani, Renamisdayani; Mulfianda, Ryan (Transpublika Publisher, 2024)
Emotional intelligence is a person's ability to regulate their emotional life with intelligence, maintaining emotional harmony and expression through the skills of self-awareness, self-control, self-motivation, empathy and social harmony. The aim of this research is to analyze the relationship between emotional intelligence and nursing professional students in Banda Aceh Aceh Besar 2023. This type of research is descriptive correlation. The population in this study was 288 nursing professional students from Banda Aceh, Aceh Besar.The sampling technique used accidental sampling with a sample size of 258. This research was carried out on 20-30 July 2023. The results of the research obtained a value for self-awareness with emotional intelligence p=value 0.013, it can be concluded that there is a relationship between self-awareness and emotional intelligence, on self-regulation p value = value 0.033 there is a relationship between self-regulation and emotional intelligence, for motivation with a value of p = value 1.000 thre is no relationship between motivation and emotional intelligence, for empathy with a value of p = value 0.000 there is a relationship between empathy and emotional intelligence, for support from parents and family p value = value 0.680, then there is no relationshipbetween family support emotional intelligence and friendship social relationships obtained p value = value 0.009, there is a relationship between friendship social relationships and emotional intelligence.